Stimulating Metacognitive and Problem Solving-Skills Students' on Chemical Equilibrium through Modified Problem-Based Learning (M-PBL) Strategy - Jusniar Jusniar; Syamsidah Syamsidah; Munawwarah Munawwarah (Jurnal Penelitian Pendidikan IPA, 2023)
This quasi-experimental aim is to examine the effect of implementing the M-PBL strategy on the metacognitive and problem-solving skills of Chemistry Education students. The number of research samples was 35 and 33 students for the experimental and control classes were selected randomly. The experiment class uses the M-PBL strategy. In contrast, the control class usages a verification strategy for Chemical Equilibrium, Advance Basic Chemistry courses in the even semester of the 2020/2021 academic year. Two instruments used are, 1) 12 items of Objective test on Chemical Equilibrium (CE) to measure students' problem-solving skills. 2) 12 Essay Test items to measure metacognitive knowledge. Assessment of metacognitive Knowledge adapts Rompayom's rubric. Implementing the M-PBL Strategy affected students' declarative, procedural, and conditional knowledge. The MPBL strategy had a better effect than conventional strategies on students' problem-solving skills.Â